PENGARUH HEAT MOISTURE TREATMENT PATI SAGU TERHADAP KARAKTERISTIK KIMIA STIK SARUT (PANGAN TRADISIONAL MALUKU) - Tetelepta, Gilian; Picauly, Priscillia (Jurnal Sains dan Teknologi Pangan, 2021)
The purpose of this research was to determine the appropriate heat moisture treatment modified with different moisture contents to produce sarut stick. A completely randomized experimental design with native sago starch and different moisture content (24%, 27%, dan 30%) and 3 replications was applied in this research. The result show that the HMT treatment of 27% was found to be the right treatment with the highest levels namely water content 2,83%, ash content of 0,87%, protein content of 2,13%, fat content 8,11%, carbohydrate content 86,06% and crude fiber content 13,16%.